Numerical Continuum Mechanics. - Kukudzhanov, V. N. (De Gruyter studies in mathematical physics., 2012)
This work focuses on computational methods in continuum thermomechanics. The text is based on the author's lectures, which ensures a didactical and coherent buildup. The main emphasis is put on the presentation of ideas and qualitative considerations, illustrated by specific examples and applications. Conditions and explanations that are essential for the practical application of methods are discussed thoroughly.